Ulam Stability for Fractional Differential Equation in Complex Domain - Rabha W. Ibrahim (Abstract and Applied Analysis)
The present paper deles with a fractional differential equation zαDzαu(z)+zu'(z)+(z2-a2)u(z)=∑n=0∞anzn+α, 1<α≤2, where z∈U:={z:|z|<1} in sense of Srivastava-Owa fractional operators. The existence and uniqueness of holomorphic solutions are established. Ulam stability for the approximation and holomorphic solutions are suggested.